Pengaruh Strategi Bahasa Persuasif Dalam Promosi Diskon Dan Voucher Tiktok Terhadap Minat Beli Mahasiswa Jurusan Administrasi Bisnis Polteknik Negeri Semarang - Merrys Margaretha Putri Reimal; Tasya Latifa Zahra; Ana Putri Nastiti (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the influence of persuasive language strategies used in TikTok discount and voucher promotions on the purchase intention of students from the Business Administration Department at Politeknik Negeri Semarang. A quantitative survey method was employed by distributing questionnaires to 60 students. The collected data were analyzed descriptively using IBM SPSS Statistics. The findings indicate that persuasive language characterized by clear wording, attractive diction, persuasive calls to action, and well-presented promotional information received positive responses from the majority of respondents. Furthermore, discount and voucher promotions increased students' interest in products, encouraged voucher usage, and strengthened their intention to make purchases. Therefore, The strategy has a positive effect on students' purchase intention.